Systemic deregulation of autophagy upon loss of ALS- and FTD-linked C9orf72 - Ji, Yon Ju (Autophagy, 2017)
A genetic mutation in the C9orf72 gene causes the most common forms of neurodegenerative diseases amyotrophic lateral sclerosis (ALS) and frontotemporal dementia (FTD). The C9orf72 protein, predicted to be a DENN-family protein, is reduced in ALS and FTD, but its functions remain poorly understood. Using a 3110043O21Rik/C9orf72 knockout mouse model, as well as cellular analysis, we have found that loss of C9orf72 causes alterations in the signaling states of central autophagy regulators. In particular, C9orf72 depletion leads to reduced activity of MTOR, a negative regulator of macroautophagy/autophagy, and concomitantly increased TFEB levels and nuclear translocation. Consistent with these alterations, cells exhibit enlarged lysosomal compartments and enhanced autophagic flux. Loss of the C9orf72 interaction partner SMCR8 results in similar phenotypes. Our findings suggest that C9orf72 functions as a potent negative regulator of autophagy, with a central role in coupling the cellular metabolic state with autophagy regulation. We thus propose C9orf72 as a fundamental component of autophagy signaling with implications in basic cell physiology and pathophysiology, including neurodegeneration.